Soybean Planting Date and Maturity Group Selection as a Method to Optimize Net Returns above Total Specified Costs and Irrigation Water Use Efficiency. Issue 1 (14th March 2019) - Wood, C. W.; Krutz, L. J.; Falconer, L.; Pringle, H. C.; Henry, W. B.; Irby, T.; Orlowski, J. M.; Gore, J.; Bryant, C. J.; Boykin, D. L.; Atwill, R. L.; Spencer, G. D.
Abstract : Core Ideas: Should soybean maturity group change as planting date progresses to improve irrigation water use efficiency? Mid‐Southern soybean producers should plant Maturity Group 4 regardless of planting date. Planting date and maturity group will interact to effect yield and irrigation water use efficiency. Sustainable withdrawal from the Mississippi River Valley Alluvial Aquifer is predicated on optimizing irrigation water use efficiency (IWUE) while, concomitantly, maintaining or improving on‐farm profitability. This research sought to determine interactions of soybean ( Glycine max L.) planting date (early, middle, and late) and maturity group (MG) (III, IV, V) on yield, net returns above irrigation costs, and IWUE. Research was conducted near Stoneville, MS on a Dundee silty clay loam from 2015–2017. Planting date and MG interacted to have an effect on yield and IWUE ( P ≤ 0.0001) but not net returns above total specified costs ( P ≤ 0.0861). Relative to planting MG IV early, planting later or switching to another MG either had no effect or reduced yield up to 33.9%. Depending on planting date, the IWUE of MG III was 4.8 to 77.1% greater than that of MG IV and V. Net returns above total specified costs were optimized by planting a MG IV in either the early or mid‐planting windows. Our data indicate that the maximum IWUE that can be attained without having an adverse effect on yield and net returns above total specified costs is achieved by planting MG IV early or mid‐season. With the use of planting date and MG selection, producers in the Mid‐Southern United States can maintain or improve on‐farm profitability while concurrently reducing groundwater withdrawals.